Rebellion of the economically depleted in the face of the ecosocial crisis. Collapse, impoverishment and growing resistance in sacrifice zones and exclusion territories - Cerdan Heredia, Rufi (Revista Española de Desarrollo y Cooperación, 2024)
The socioecological crisis is generating new forms of social exclusion that are driving many people around the world to the margins of society, but they are also provoking forms of popular resistance to confront it. The environmental debate focuses on the institutional policies needed to halt the collapse, but it does not reflect either the current reality of the excluded or their increasingly organized role in the so-called "territories of sacrifice" and in the "territories of exclusion." These experiences, which I call the rebellion of the diminished, are showing their capacity for self-organization and political advocacy aimed at a change of system.